Ecotoxicological Investigation in Three Model Species Exposed to Elutriates of Marine Sediments Inoculated With Bioplastics - Campani, Tommaso; Casini, Silvia; Caliani, Ilaria; Pretti, Carlo; Fossi, Maria Cristina (Frontiers in Marine Science, 2020)
The aim of this study was to evaluate a set of ecotoxicity biotests on three marine model species exposed to elutriates of marine sediments inoculated with the biodegradable plastic Mater-Bi or with cellulose. The sediments were incubated at 28°C and tested after 6 months, when clear signs of degradation were visible in the exposed samples, and after 12 months, when the samples had completely disappeared. The model organisms selected for the study were the unicellular algae Dunaliella tertiolecta, the sea urchin (Paracentrotus lividus) and sea bass (Dicentrarchus labrax) juveniles. The unicellular algae and sea urchins were used to determine the toxicological endpoint of growth inhibition and embryotoxicity, respectively, and the sea bass juveniles were tested to evaluate sublethal effect endpoints using lipid peroxidation and genotoxicity biomarkers. Elutriates of sediment inoculated with Mater-Bi for 6 and 12 months showed an absence of toxic effects in all of the model organisms exposed in this study. The Mater-Bi degradation process did not generate or transfer into the elutriates toxic substances that could cause alterations in the growth of D. tertiolecta, in the P. lividus embryo-toxicity assay or in the sensitive biomarker responses of the fish Dicentrarchus labrax. The results obtained in this study suggest that the ecotoxicological approach applied may be suitable for investigating the environmental impact of the degradation of bioplastics in marine sediments.